The safety and efficacy of alfentanil-based induction in bronchoscopy sedation: A randomized, double-blind, controlled trial. Issue 43 (October 2016) - Hsieh, Chung-Hsing; Lin, Ting-Yu; Wang, Tsai-Yu; Kuo, Chih-Hsi; Lin, Shu-Min; Kuo, Han-Pin; Lo, Yu-Lun
Abstract: Background: Alfentanil in combination with propofol produces a synergistic sedative effect in patients undergoing flexible bronchoscopy (FB). However, the use of this combination is controversial due to the risk of cardiopulmonary depression. The aim of this study was to evaluate the proper induction regimen of alfentanil in propofol target-controlled infusion for FB sedation. Methods: One hundred seventy-three patients were assigned randomly into 5 regimens: Group 1 and 2, alfentanil 2.5 and 5 μg/kg, respectively, immediately before propofol administration; Group 3 and 4, alfentanil 2.5 and 5 μg/kg, respectively, 2 minutes before propofol administration; and Group 5, propofol administration alone to achieve the observer assessment of alertness and sedation scale 3∼2. The bronchoscopists, physicians in charge of sedation, and patients were blind to the regimens. Adverse events, drug dose, induction, procedure and recovery time, cough severity, and propofol injection related pain were recorded. Results: The patients in groups 2 and 4 required a lower dose of propofol ( P = 0.031 and 0.019, respectively) and shorter time ( P = 0.035 and 0.010) than group 5 for induction. Patients in group 2 experienced more hypoxemia than those in group 5 during induction ( P = 0.031). The physician in charge of sedation scored a lower severity of cough in the patients in group 4 than in groups 3 and 5. There were no differences in terms of propofol injection related pain among the groups. Conclusion: Alfentanil 5 μg/kg given immediately before propofol infusion cannot be recommended. Further study is required to define conclusions about alfentanil 2.5 and 5 μg/kg because of the low power rating of subgroup in the present study.